Speciation of inorganic phosphorus in some bench-merk soils of Bangladesh - Chowdhury, P; Hoque, S; Parvin, A; Moniruzzaman, M (Bangladesh Journal of Scientific and Industrial Research, 2018)
To study the phosphorus transformation in soils, experiment was conducted in the laboratory. In this study, three different bench-mark soil series of three different Agro-ecological Zones namely, Brahmaputra (Jamuna) floodplains (Dhamrai series, Areni-Eutric gleysols), Low Ganges River Floodplain (Ishurdi series, Chromi-calcaric Gleysols), and Madhupur Tract (Tejgaon series, Chromi-Calcaric Gleysols ) of Bangladesh were selected. For conducting this experiment, all the determination was performed triplicate. The changes of phosphorus fractions were discussed. Soil Phosphorus pools were assessed by sequential P fractionation on days 0, 7, 20 and 40. The inter conversions of different P- fractions were noticed during the course of incubation experiment. The magnitude of these changes differed among soils, being greatest in the Dhamrai soil. Principal component analysis of the data showed that the size of the P pools was related to soil properties; high concentrations of Ca-P were associated with high pH and calcium concentrations, high concentrations of Fe-P and residual P were correlated with high aluminium. It can be concluded that soil P pools can be generalized across the three soil used in this study, but that the size of the P pools is affected by soil properties. Bangladesh J. Sci. Ind. Res.53(1), 7-12, 2018